1998
DOI: 10.1103/physrevlett.81.3347
|View full text |Cite
|
Sign up to set email alerts
|

Study of Unimolecular Reactions by Coulomb Explosion Imaging: The Nondecaying Vinylidene

Abstract: Isomerization of a highly excited vibrational state of acetylene was studied using the Coulomb explosion imaging technique. A vinylidene isomer was prepared by electron photodetachment of the negative molecular ion and the corresponding distribution function of the nuclear configurations of the molecule was sampled after a time period of 3.5 ms. The population of the vinylidene isomer was found to be significantly high (ϳ50%), in contrast to the commonly accepted notion of vinylidene as a short-lived isomer. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 15 publications
6
83
0
Order By: Relevance
“…Once the laser strips electrons from the molecule, the remaining positively charged structure can explode, creating a molecular plasma cloud. Coulomb explosion can be used to generate bright keV x-ray photons [14,15], highly energetic electrons [16], and for imaging [17][18][19].The strong-field ionization and fragmentation of hydrocarbon molecules is a prototypical example of the Coulomb explosion of polyatomic molecules, and it has been the subject of several experiments [9,11,[20][21][22][23]]. An important quantity measured in these experiments is the kinetic energy distribution of the protons ejected during the fragmentation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once the laser strips electrons from the molecule, the remaining positively charged structure can explode, creating a molecular plasma cloud. Coulomb explosion can be used to generate bright keV x-ray photons [14,15], highly energetic electrons [16], and for imaging [17][18][19].The strong-field ionization and fragmentation of hydrocarbon molecules is a prototypical example of the Coulomb explosion of polyatomic molecules, and it has been the subject of several experiments [9,11,[20][21][22][23]]. An important quantity measured in these experiments is the kinetic energy distribution of the protons ejected during the fragmentation.…”
mentioning
confidence: 99%
“…Once the laser strips electrons from the molecule, the remaining positively charged structure can explode, creating a molecular plasma cloud. Coulomb explosion can be used to generate bright keV x-ray photons [14,15], highly energetic electrons [16], and for imaging [17][18][19].…”
mentioning
confidence: 99%
“…We would like to discuss our work in light of a recent study of vinylidene by Coulomb explosion imaging, 37 where it was found that 3.5 s after production of vinylidene, the population of the vinylidene isomer is still 50%. The framework given by the authors of Ref.…”
Section: H 2 Results-density Of States Analysismentioning
confidence: 99%
“…First, consider once again the acetylene-vinylidene isomerization. In Coulomb explosion experiments, 46 the molecule is prepared in the The Dance of Molecules Kellman and Tyng vinylidene form. Astonishingly, the system appears to cycle back and forth between the vinylidene and acetylene forms of Figure 6 for several microseconds.…”
Section: Energy Flow and Chemical Reactivitymentioning
confidence: 99%